2010
DOI: 10.1111/j.1741-5705.2010.03781.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Monikers: The Role of Name Presentation in the 2008 Presidential Election

Abstract: Given America's widespread contempt for Islamic extremists, Obama's Muslim‐sounding moniker could have cost him electoral support. Consequently, anecdotal evidence suggests that Obama played a “name game” in which he deflected suspicions about his religious background by avoiding use of his middle name (Hussein) and minimizing the frequency with which his opponents used it. Did the presentation of Obama's name affect how voters evaluated him? Results from a web‐based experiment suggest that the answer varies b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A number of studies have demonstrated the influence of symbolic racism on political attitudes (Kinder and Sanders 1996; Sears et al 1999; Kinder and Mendelberg 2000; Rabinowitz et al 2009) and support for Republican presidential candidates (Tesler and Sears 2010; Kinder and Dale-Riddle 2012). Symbolic racism has also been shown to have a negative effect on support for Barack Obama (Block and Onwunli 2010; Lewis-Beck, Tien, and Nadeau 2010; Piston 2010) and a positive effect on support for Donald Trump (Luttig, Federico, and Lavine 2017; Hooghe and Dassonneville 2018; Major, Blodorn, and Major Blascovich 2018; Schaffner, Macwilllams, and Nteta 2018; Setzler and Yanus 2018).…”
Section: Trumpian Politics: Racism Sexism and Resentment Of Social Ch...mentioning
confidence: 99%
“…A number of studies have demonstrated the influence of symbolic racism on political attitudes (Kinder and Sanders 1996; Sears et al 1999; Kinder and Mendelberg 2000; Rabinowitz et al 2009) and support for Republican presidential candidates (Tesler and Sears 2010; Kinder and Dale-Riddle 2012). Symbolic racism has also been shown to have a negative effect on support for Barack Obama (Block and Onwunli 2010; Lewis-Beck, Tien, and Nadeau 2010; Piston 2010) and a positive effect on support for Donald Trump (Luttig, Federico, and Lavine 2017; Hooghe and Dassonneville 2018; Major, Blodorn, and Major Blascovich 2018; Schaffner, Macwilllams, and Nteta 2018; Setzler and Yanus 2018).…”
Section: Trumpian Politics: Racism Sexism and Resentment Of Social Ch...mentioning
confidence: 99%
“…This negative attitude toward outsider groups, therefore, could have a significant effect on protest voting. Previous research has shown that racist resentment remains an important voting motive, which had a negative effect on support for Barack Obama in 2008 (Block and Onwunli 2010; Piston 2010). The virulent attacks that Trump directed against “Mexican immigrants” during the campaign are an interesting development.…”
Section: Expanding the “Michigan” Model: Protest Voting Racist Resenmentioning
confidence: 99%
“…In addition, a study by Barry A. Hollander (2010) showed that political conservatives who were not black, had lower levels of education, and subscribed to biblical literalism were likely to subscribe to the Obama as Muslim rumor (also see Block and Onwunli 2010). Attempts to mark political opponents as "other" are certainly not new.…”
Section: Obama As Othermentioning
confidence: 99%